Determination of Phytochemical in Extracted Punica Granatum Peels and its Efficacy of Healing Burn Injuries - Siti Nudra Shafinie, Ab Aziz (2013)
Natural plants have been used as a traditional medicine all over the world. One of these natural plants is pomegranate (punica granatum). This study aimed to determine the phytochemicals from Pomegranate peels that can heal burn wounds by extracting the peels. Additionally, this study is investigating the efficiency of Pomegranate (Punica granatum) in curing the burn wounds compare to the commercial ointment. Extracting the pomegranate start with drying the peels under room temperature, followed by drying in the oven for 48 hours with the temperature of 50oC, then grinding them. However, after the preparation of the ointment from the peels fine powder, four different samples of rats were burnt and treated. The result of the extract and the analysis showed that pomegranate is reach by an active constituent such as Saponin, Glycosides, Steroids and Terpenoid which play the main role in healing the burn wounds. This claimed is supported by the result of the treatment observations of the rats' samples which proof that the efficiency of using pomegranate ointment in curing the wounds is higher and faster than the commercial ointment. As conclusion the objective of this study has been achieved, and positive result has been obtained.